2017
DOI: 10.1177/2156759x18773591
|View full text |Cite
|
Sign up to set email alerts
|

Black Male School Counselor Educator Contextual Explorations in Leadership

Abstract: The counseling profession has seen an increase in research exploring counselor educators’ professional identity development. Leadership skills are noted in the Council for Accreditation of Counseling and Related Educational Programs standards as an important part of a school counselor’s identity, but scholars have paid less attention to leadership identity development for counselor educators. This lack of emphasis in the literature is even more evident when considering the leadership development of racial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…As members of the counseling profession strive to integrate multicultural competence and social justice into their research and practice, this commitment should be rooted in the plight of oppressed people (Henfield, Washington, Rue, & Byrd, 2018). This means recognizing how disregarding the narratives of people from nondominant intersecting subject positions (e.g., race, class, gender, sexual orientation) contributes to their ongoing marginalized status.…”
Section: Resultsmentioning
confidence: 99%
“…As members of the counseling profession strive to integrate multicultural competence and social justice into their research and practice, this commitment should be rooted in the plight of oppressed people (Henfield, Washington, Rue, & Byrd, 2018). This means recognizing how disregarding the narratives of people from nondominant intersecting subject positions (e.g., race, class, gender, sexual orientation) contributes to their ongoing marginalized status.…”
Section: Resultsmentioning
confidence: 99%
“…Female counselor educators represent diverse racial/ethnic backgrounds (CACREP, 2018). Cultural backgrounds may influence the leadership characteristics of people of color (Ayman, 1993;Chin, 2013); however, cross-cultural leadership in counselor education remains a relatively unexplored area (Henfield et al, 2017). Intersectionality (Crenshaw, 1989) is a theoretical framework that contends that individuals have identities (e.g., race, gender, class, sexuality) that intersect in ways that impact how they are understood and treated.…”
Section: Cross-cultural Leadershipmentioning
confidence: 99%
“…Shao and Webber (2006) found that culture could be important to consider when studying transformational leadership. Black male counselor educators have noted that racial/ ethnic identity and contextual factors must be recognized as part of one's leadership identity (Henfield et al, 2017). Sanchez-Hucles and contemporaries maintain that "to ignore aspects of identity as unimportant is to tacitly advantages the leadership behavior of the dominant group in the organization under study (p.…”
Section: Cross-cultural Leadershipmentioning
confidence: 99%
“…Although multiple factors are considered for tenure, the feedback Black faculty receive from colleagues and students is critical. The formal and informal messages they receive can reinforce isolation, discrimination, and a sense of not belonging (Henfield, Washington, De La Rue, & Byrd, 2018;Jackson & Crawley, 2003;B. P. Smith & Hawkins, 2011;Tuitt, 2012;Vereen & Hill, 2008;Woodson & Pabon, 2016).…”
Section: Black Faculty Pursuit Of Tenurementioning
confidence: 99%